(untitled) (Materiali di Estetica. Terza serie, 2017)
The essay attempts to compose elements of the Jünger-type theory with some of the first Marx’s suggestions on the Feuerbachian concept of the Gattungswesen. It is in question, on the background, a new theory about role and nature of the subject in the revolutionary process.